A MINI-REVIEW OF KINETIC STUDY ON SHOULDER JOINT USING KUKA LIGHTWEIGHT ROBOT (Journal of Pharmaceutical Negative Results, 2022)
A Traditional physiotherapy sessions are long and demanding, requiring a lot of effort and time from both the physiotherapist and the patient. The KUKA LWR's high work capacity and consistent precision of end- effector location and movement were utilized to solve these issues. The KUKA LWR is a seven-degrees-of- freedom robotic manipulator designed for applications in which the robot must be near the human operator. During shoulder flexion exercises, which are commonly employed in traditional physiotherapy sessions, the robotic system pretends to analyze upper-limb behaviour, specifically the shoulder complex.